Durian Culinary Products Based on Local Food as a Culinary Tourism Attraction in Medan City - Imran Yasin, M. Try; Muhamad, Muhamad (Jurnal Toursci, 2023)
As the capital of North Sumatra, Medan City has an image that is quite attached to durian culinary destinations. This can be seen from the many culinary businesses that make durian their flagship product so that it can become an icon of culinary tourism in Medan. This study aims to identify the characteristics of the attractiveness, management, and promotion mix of culinary tourism products in three leading durian outlets in Medan City: Ucok Durian, Pelawi Durian, and Durian Ucok Tanjung. The method used in this study is exploratory qualitative with data collection techniques using in-depth interviews, observations, literature studies and documentation. The advertising promotion mix involves social media, print media, electronic media, and display signs. The sales promotion method is offered through free trials, discounts, and attractive promos during the durian season. Managers carry out The personal selling method whenever they fill in trade shows and festivals. The public relations method is carried out through collaboration with durian agents, being a seminar and media resource person, and becoming a sponsor for an activity.